Social Media as A Marketing Tool for Healthcare Providers: A Literature Study - Kharisma Ersha Mufti; Amal Chalik Sjaaf; Andari Rahmani Putri (Jurnal KESANS : Kesehatan dan Sains, 2022)
Introduction: The use of social media as a marketing tool has only grown in the last decade, so social media research has mostly focused on defining what it is through explaining the new terminology and concepts that form its foundation and exploring the impact of health care integration of social media on the behavior of health care users. Methods: This literature focuses on being able to describe what social media marketing is and to find out what factors influence the behavior of health service users relative to social networks by using the literature study or literature review method Objective: Approaches to communicating with health care users have changed a lot with the advent of social media. Therefore, health care workers must learn how to use social media in a manner that is consistent with their work plan. Result and discussion: Is that the technology readiness of health service users is important to be remembered by health services when marketing on social networks in the context of product marketing. Conclusion: Health service providers as health services must be able to market comprehensive services through social media properly as a means of expanding networks in order to provide the best service.